Perfil da fluência e frequência da gagueira do desenvolvimento persistente familial - Nogueira, Paula Roberta [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Stuttering is a fluency disorder characterized by excessive atypical ruptures in the linguistic formulation, in which a person has difficulty in producing smooth speech. Genetic factors may be involved in the stuttering transmission. In this sense, objective assessments and family history plays a key role in both the initial diagnosis and in controlling disease progression. Accordingly, the purpose of this study was to characterize the fluency profile of individuals with familial persistent developmental stuttering and determine the familial and sexual frequency of the disorder in the family. Participants were 100 individuals with familial persistent developmental stuttering of both gender, aged 5-59 years, with the following inclusion criteria: stuttering complaining, onset of stuttering must have occurred during childhood, minimum duration of 36 months typical of stuttering-like disfluencies, present minimum of 3% of stuttering-like disfluencies, minimum score of 11 points (children) or 18 points (teenagers aged 17 and over) in the Stuttering Severity Instrument - SSI-3. The following procedures were used: clinical and familial history, fluency assessment and Stuttering Severity Instrument. Statistical analysis was performed using specific tests to compare the variables in the different age groups, as well as a comparison of their female and male. Our results showed about 13.25% of all disfluencies and 6.92% of stuttering-like disfluencies. The mild severity was the most common (45%). There was a significant difference in the frequency of stuttering in male relatives over female (p = 0.042). We conclude that the fluency profile showed different characteristics when compared to the fluency profile of fluency. However, findings on the speech rate were dispersed and not conclusive with respect fluents. Stuttering individuals showed greater prevalence of stuttering-like disfluencies in respect to other disfluencies. Regarding the stuttering...

Gagueira é um distúrbio da fluência caracterizado pelas rupturas atípicas excessivas na formulação linguística, prejudicando a suavidade da fala. Fatores genéticos podem estar envolvidos na transmissão da gagueira. O objetivo deste estudo foi caracterizar o perfil da fluência de indivíduos com gagueira do desenvolvimento persistente familial e determinar a frequência familial e sexual do distúrbio nos familiares. Participaram 100 indivíduos com gagueira do desenvolvimento persistente familial, de ambos os sexos, na faixa etária de 5 a 59 anos, com os seguintes critérios de inclusão: queixa de gagueira, o inicio do distúrbio deve ter ocorrido durante a infância, duração mínima de 36 meses das DTG (disfluências típicas da gagueira), apresentar mínimo de 3% de DTG, pontuação mínima de 11 pontos (crianças) ou de 18 pontos (adolescentes acima de 17 anos) no Instrumento de Gravidade da Gagueira (Stuttering Severity Instrument - SSI- 3. Os procedimentos utilizados foram: história clínica e familial, avaliação da fluência e Instrumento de Gravidade da Gagueira. A análise estatística foi realizada por meio de testes específicos para comparação da variáveis nas diferentes classes etárias, bem como para comparação em relação ao sexo feminino e masculino. Os resultados mostraram uma média de 13,25% do total das disfluências e 6,92% de disfluências típicas da gagueira. A gravidade leve foi a mais frequente (45%). Houve diferença significativa na frequência da gagueira em familiares do sexo masculino em relação ao feminino (p= 0,042). Pode-se concluir que o perfil da fluência apresentou características diferentes do perfil da fluência de fluentes. Indivíduos com gagueira manifestaram maior quantidade de disfluências típicas da gagueira e do total de disfluências quando comparados com fluentes. No entanto, os achados sobre a taxa de elocução foram diversos e não conclusivos com relação aos ...
Keywords: Fonoaudiologia; Fala; Disturbios da fala; Gagueira - Aspectos genéticos; Speech